Iodine-mediated one-step synthesis of ipomone from gibberellic acid - Goel, Bharat; Tripathi, Nancy; Bhardwaj, Nivedita; Jain, Shreyans K. (Taylor and Francis Ltd., 2022)
A fast and efficient method for synthesising ipomone (4), a bicyclo[3.2.1]octanone containing aromatised derivative, from gibberellic acid (1) has been developed using molecular iodine as a mild and effective mediator under heating conditions in a single step. Evidence was obtained that the reaction simultaneously proceeds through aromatisation and pinacol-pinacolone type 1,2-alkyl shift. Use of excess iodine afforded iodomethyl derivative (5) that could serve as starting material for the synthesis of additional analogs.
This paper published with affiliation IIT (BHU), Varanasi in Open Access Mode.
Keywords: 1,2-alkyl shift; gibberellic acid; iodination; ipomone; natural product